Evaluation of certain bioactive compounds using in ovo diabetic model (Journal of Laboratory Animal Science, 2024)
Mammalian models are frequently used for drug research and delivery systems. However, valid mammalian  models are expensive, time consuming and not easy to set up and evaluate. Furthermore, they are often linked  with ethical and legal aspects. Many micro, macro nutrients and other photochemical from food materials  are found to possess many desirable health benefits. A large number of studies involving animals have  been carried out to explore these beneficial properties. As an alternative, chick embryo developed through  incubation of fertile chicken eggs has been used as a novel system to develop suitable models for biochemical  and neutraceutical research. The in ovo technique is accepted as an alternative to traditional mammalian  models and this can be suitably used in our routine biochemical tests, wherever the animal trials are not  feasible. In view of the above, the development and evaluation of certain bioactive components using in ovo technique as a diabetic model was carried out in our laboratory. Bixin decreased significantly the plasma  glucose, triglycerides, cholesterol, urea, creatinine and blood urea nitrogen, while liver glycogen levels in  treated diabetic chick embryos increased when compared to control diabetic chick embryos.
Keywords: environmental; enrichment,; welfare,; stress,; animal behavior